Intestinal rehabilitation with ultrashort bowel syndrome due to necrotizing fungal enteritis - Raphael H. Parrado; Nathan S. Rubalcava; Clive Miranda; J. Craig Egan (Elsevier, 2021)
Introduction: Ultra-short bowel syndrome (USBS) was once considered incompatible with life. It can be secondary to multiple cases but most rarely infection or autoimmune disease. Case: We discuss a 13-yr old female with Polyarteritis Nodosa complicated by a necrotizing fungal infection due to C. tropicalis who developed USBS after requiring extensive resection of her bowel, omentum and abdominal wall due to an invasive fungal infection, leaving her with less than 5 cm of jejunum and residual left colon. With intestinal rehabilitation she was able to be weaned down to 70% enteral nutrition and 30% TPN. Conclusion: Ultra-short bowel syndrome is increasing in the pediatric population as rates of survival continue to improve. After management of the acute disease, in this case severe infection and vascular disease, long term management with a focus on providing high-quality multidisciplinary intestinal rehabilitation is vital as well as minimizing PN complications.